O uso da cartografia temática nos estudos do comportamento religioso na microrregião de Maringá-PR - Boava, Alex Pires (2014)
This project aimed to map the religious demographic situation and the locations of worship and praise in the microregion of Maringá, Parana state, as well as understand the spatial behavior of the religious pluralism present in this study area. Graphic treatment techniques, such as sortable matrix, binder-image and range of curve, to design and development of the synthesis maps were used. After successive syntheses maps, we obtained a final representation of the religious landscape in the studied area. This representation showed that the municipalities of Paiçandu and Sarandi have predominance of evangelical religions regarding demographical aspects and number of churches. Moreover, these cities have a large percentage of young and needy people in all religious categories analyzed. The municipalities of Mandaguari e Marialva have a marked territoriality focused on Roman Catholic even with a moderate growth of other religiosity in recent censuses. However the percentage of elderly residents and people living in rural areas has been found in all categories analyzed. Maringa city have been characterized by the presence of a high religious diversity. In all categories analyzed was observed a significant percentage of people with high purchasing power and high level of education, even with an intense religious plurality, the rate of apostolic Roman Catholics remained stable with only a slight decrease. This initiative will contribute to other studies related to religion, considering the diffusion and diversification of religions present in this region in recent times. Thus, this factor has been becoming a very important element in the geographic area studied. Cartographic representation was supported by geoprocessing techniques and methodologies developed by Jacques Bertin (1983) for the preparation of subtitles.